The REAnimation Low Immune Status Markers (REALISM) project: a protocol for broad characterisation and follow-up of injury-induced immunosuppression in intensive care unit (ICU) critically ill patients. Issue 6 (21st June 2017) - Rol, Mary-Luz; Venet, Fabienne; Rimmele, Thomas; Moucadel, Virginie; Cortez, Pierre; Quemeneur, Laurence; Gardiner, David; Griffiths, Andrew; Pachot, Alexandre; Textoris, Julien; Monneret, Guillaume
Abstract : Introduction: The host response to septic shock is dynamic and complex. A sepsis-induced immunosuppression phase has recently been acknowledged and linked to bad outcomes and increased healthcare costs. Moreover, a marked suppression of the immune response has also been partially described in patients hospitalized in intensive care unit (ICU) for severe trauma or burns. It has been hypothesized that immune monitoring could enable identification of patients who might most benefit from novel, adjunctive immune-stimulating therapies. However, there is currently neither a clear definition for such injury-induced immunosuppression nor a stratification biomarker compatible with clinical constraints. Methods and analysis: We set up a prospective, longitudinal single-centre clinical study to determine the incidence, severity and persistency of innate and adaptive immune alterations in ICU patients. We optimized a workflow to describe and follow the immunoinflammatory status of 550 patients (septic shock, severe trauma/burn and major surgery) during the first 2 months after their initial injury. On each time point, two immune functional tests will be performed to determine whole-blood TNF-α production in response to ex vivo lipopolysaccharide stimulation and the T lymphocyte proliferation in response to phytohaemagglutinin. In addition, a complete immunophenotyping using flow cytometry including monocyte HLA-DR expression and lymphocyte subsets will be obtained. New markers (ie, levels of expression of host mRNA and viral reactivation) will be also evaluated. Reference intervals will be determined from a cohort of 150 age-matched healthy volunteers. This clinical study will provide, for the first time, data describing the immune status of severe ICU patients over time. Ethics and dissemination: Ethical approval has been obtained from the institutional review board (no 69HCL15_0379) and the French National Security agency for drugs and health-related products. Results will be disseminated through presentations at scientific meetings and publications in peer-reviewed journals. Trial registration number: Clinicaltrials.gov Registration number: NCT02638779 . Pre-results.